Rekonstruksi Kalimat pada Teks Berita di Laman CNN Indonesia Edisi Desember 2023 sebagai Bahan Ajar Membaca Kritis Siswa Kelas 12 SMA - Nabila Dila Ardiyanti; Ahmad Ma’arijul Amri; Yulian Akbar Rizki Nur Fazri; Ika Apriliani; Alifia Khoirun Nisa; Asep Purwo Yudi Utomo; Uki Hares Yulianti (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
News is a text that has an important role in disseminating information. News text is so useful that it has become a literacy material for students due to the development of advanced technology. Although it has become one of the sources of student literacy, online news texts are still classified as having syntactic errors such as a lack of understanding of the language used in compiling a sentence in the news. The purpose of this study is to describe sentence errors in the news contained in the old CNN Indonesia news, such as "December Sky Phenomena: Geminid Meteor Shower to Solstice", "Mandalika Circuit's Important Role in Bringing Indonesian Drivers to Success in Asia", "Solar Storms Raining on Earth, RI Safe?", "The First Candidate Debate will be Held at the KPU Office on December 12", and "When HIV Tests Become a Scary Scourge Because of People's Scorn". This research uses a descriptive method with a qualitative approach. The results of this study found several findings such as effective sentences, ineffective sentences, spelling errors according to EYD, errors in the use of diction, and sentences that are not clear to the reader. The most common error found in the five news articles is ineffective sentences. The benefit of this research is to provide knowledge insights in the form of understanding sentence writing systematically, which will be useful in improving understanding of authorship in news texts and preventing errors from occurring again in the same news so that it is worthy of being a literacy material for 12th grade high school students.